Assessment of Pentraxin 3 Level in Gingival Cervicular Fluid of Chronic Periodontitis Patients Before and after non-Surgical Periodontal Therapy - Ahlam Ali Elburnat; Amr Zahran; Olfat Shaker; Shahira Elashiry (Cairo : Ahlam Ali Elburnat, 2013)
The aim of the present study was to assess the diagnostic value of MCP-3 in periodontal diseases by : 1 Determining the concentration of MCP-3 in GCF from active sites of periodontal destruction in patients suffering from chronic periodontitis as compared to normal control patients . 2 Comparing between MCP-3 levels in GCF samples from active sites before and after supragingival and subgingival debridment. Materials and Methods: This study was conducted on 30 subjects divided into 10 individuals with healthy periodontium and 20 patients suffering from chronic periodontitis, where the level of MCP-3 has measured before and after non-surgical therapy, with 6 weeks follow up. Clinical recordings (GI, PI, PD, CAL) were scored for each participant in the study before and after treatment. GCF samples were obtained from each patient included in the present study and the amount of MCP-3 in the GCF samples was determined using commercially available human-specific ELISA that were in accordance with the manufacturer{u2019}s instructions (total MCP-3 ELISA kit
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Periodontology
Issued also as CD
Keywords: Chemokines; MCP-3; Periodontal disease / periodontitis